Multi-agent systems and agreement technologies : 13th European Conference, EUMAS 2015, and third International Conference, AT 2015, Athens, Greece, December 17-18, 2015, Revised selected papers /: 13th European Conference, EUMAS 2015, and third International Conference, AT 2015, Athens, Greece, December 17-18, 2015, Revised selected papers. (2016) - Unknown
No abstract available